Automated patient health monitoring and notification system for hospital - Tan, Dorothy Xie Ying (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Wireless sensor network is now gammg attention in technology field as it has great potential to improve human's life especially in medical field. Furthermore, with the great increase in healthcare cost and patient population in medical centers, patient monitoring services using wireless technologies is considered one of the most effective solutions to improve healthcare quality as well as setting healthcare services to the minimum level. By implementing wireless technology into patient monitoring system, patients' vital health parameters such as heart pulse, blood pressure and temperature can be monitored continuously without the need to be connected to multiple wired devices in the ward. Patients will have the freedom to stay mobile while their medical ailment is being monitored conveniently as long as they are inside the hospital premises. This system is simple to use and is proposed for automated and continuous patient health monitoring that it performs analysis by integrating all of the health parameter to identify patient's current health status and also provide graph pattern recognition to support medical staff in decision making and ease analysis process. Notification will be sent to the right person at the right time.